United States Department of the Interior, draft environmental impact statement, proposed North Atlantic lease offering, February 1984 - United States. Minerals Management Service. Atlantic OCS Region. ([New York, N.Y.] : The Region, 1983)
"June 1983." Cover title: Proposed February 1984 North Atlantic outer continental shelf oil and gas lease offerings. Includes bibliographies. Mode of access: Internet.